Towards a highly adaptive software-defined radio transmitter for small satellite platforms. (September 2021) - Pätschke, Susann; Klinkner, Sabine
Abstract: The Institute of Space Systems (IRS) of the University of Stuttgart is currently analysing a mission to explore the inner Van Allen radiation belt using a small satellite of about 60 kg. The satellite shall be launched to an orbit of approximately 600 km and then use its orbital control system to reach an elliptical orbit of 330 km × 2500 km. In addition to the scientific mission goals, the mission shall demonstrate new components in the harsh radiation environment; these include an orbit control system using water-based propulsion, a highly integrated core avionic system and a ham radio X-Band data downlink system. The data downlink system for this mission is currently being developed at the IRS. Due to the highly elliptic final orbit, the need for an adaptive data downlink transmitter platform arises, that is capable of adapting its waveform to the current link conditions. Moreover, this transmitter shall be fully compliant with the Consultative Committee for Space Data System (CCSDS) recommendations for the physical and the data link layers while implementing the adaptive coding and modulation of the Digital Video Broadcast – Second Generation (DVB-S2) standard. Furthermore, this development focusses on low-power consumption, use of commercial-off-the-shelf components, re-configurability and miniaturisation. The transmitter platform is based on a System on a Chip which implements the CCSDS as well as the DVB-S2 protocol stacks. The analog components are chosen to provide possible scaling of the platform to commercial X-Band, Ku and Ka -Band. The transmitter is able to support data rates up to 200 Mbps and delivers up to 2 Watts RF power. The use of the DVB-S2 standard allows to increase the downlink capacity by 66% using variable coding and modulation. An increase by 130% or even more is possible using adaptive coding and modulation. This adaptive platform is crucial for the mission success in order to transmit the high data volume, which could not be downlinked with a platform using a fixed waveform only. The increase in downlink capacity by adapting to the link conditions can also be useful for other missions, e.g. where ground terminals are located in regions with high rain loss or for satellite constellations where each satellite has limited ground station contact. The development of this transmitter platform that can be adapted in nearly-real time to the existing link conditions is presented in this paper. Highlights: Adaptable software-defined radio transmitter which in nearly-real time adapts to the optimum transmission configuration. Use of commercial-off-the-shelf components for a software-defined radio in a medium-earth orbit. Use of the amateur radio X-band (10.45-10-5 GHz) as a proof of concept on a small satellite in the MEO.